miR-185 and miR-29a are similarly expressed in the bronchoalveolar lavage cells in IPF and lung cancer but common targets DNMT1 and COL1A1 show disease specific patterns - Bibaki, Eleni (Mol Med Rep, 2018)
Idiopathic pulmonary fibrosis (IPF) and lung cancer (LC) constitute two progressively devastating lung diseases with common risk factors including aging and smoking. There is an increasing interest in the investigation of common pathogenic mechanisms between IPF and LC with therapeutic implications. Several oncomirs, microRNAs associated with malignancy, are also linked with IPF. miR-29a and miR-185 downregulation is probably involved both in carcinogenesis and fibrogenesis. We have previously observed miR-29a and miR-185 downregulation in IPF cells from bronchoalveolar lavage (BAL) and in this study we investigated their expression in LC BAL cells. Common targets of miR-29a and miR-185 such as DNA methyltransferase (DNMT)1, DNMT3b, COL1A1, AKT1 and AKT2 were measured. Potential correlations with pulmonary function tests, smoking status and endobronchial findings were investigated. Similar levels of miR-29a and miR-185 were detected in IPF and LC while their common targets AKT1 and DNMT3b were not found to differ, suggesting potential pathogenetic similarities at the level of key epigenetic regulators. By conrast, COL1A1 mRNA levels were increased in IPF suggesting a disease-specific mRNA signature. Notably, DNMT1 was downregulated in the LC group and its expression was further reduced in the presence of increasing malignant burden as it was implied by the endobronchial findings.